2020
DOI: 10.1136/gpsych-2020-100231
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs towards the COVID-19 pandemic among patients with emotional disorders in China

Abstract: BackgroundThe novel coronavirus disease 2019 (COVID-19) pandemic has given rise to fear and panic in the public. Although hospitals in China reduced outpatient visits and restricted inpatient admission to lower the risk of transmission of COVID-19, this has significantly affected patients in need of medical attention, for example, patients with emotional disorders.AimsThis study aimed to compare the beliefs towards COVID-19 among outpatients with emotional disorders (ie, anxiety or depression) with those of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…In another study, anxiety disorder patients did not exhibit with marked psychological impact secondary to COVID-19 18 . According to Gao et al, 43.2% of patients with emotional disorder were affected, similar to our nding 13 . One explanation we proposed would contribute to this result: negative news like the virus might strike again during the upcoming winter trigger a series of emotional stress responses including anxiety and fear since these stable patients could easily access the Internet and media.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In another study, anxiety disorder patients did not exhibit with marked psychological impact secondary to COVID-19 18 . According to Gao et al, 43.2% of patients with emotional disorder were affected, similar to our nding 13 . One explanation we proposed would contribute to this result: negative news like the virus might strike again during the upcoming winter trigger a series of emotional stress responses including anxiety and fear since these stable patients could easily access the Internet and media.…”
Section: Discussionsupporting
confidence: 90%
“…This ongoing public health crisis reduced outpatient visits and hindered patients from obtaining timely medication. The previous study conducted by Gao et al found that 70% of outpatients with emotional disorders had to postpone their mental health treatment, and had more negative expectations towards COVID-19 13 . However, there remains few research on investigating the in uence of COVID-19 pandemic on psychiatric patients in stable condition; and the published surveys were about the psychological impacts in the early stage of the outbreak.…”
Section: Introductionmentioning
confidence: 94%
“…Given that, people are becoming more and more anxious with the fear of getting infected and therefore may start to keep themselves away from hospitals, even if they have serious conditions. 21 In a huge biosocial crisis such as the COVID-19 pandemic, more professional and holistic approaches are required to control the health care system. In this context, activating the telehealth system may be promising.…”
Section: Complicated Ureteral Stones During Covid-19 Eramentioning
confidence: 99%
“…The WSQ Scale has acceptable reliability and validity and the detailed procedure of its psychometrics were reported in a previous manuscript. 24 The scale consists of three dimensions as follows: self-worries, self-prevention strategies and confidence. The scale at two waves were 0.62 and 0.66 respectively, which were acceptable as an explorative questionnaire.…”
Section: Methodsmentioning
confidence: 99%